Development of microcomputer protection and measuring-control device for 35 kV distribution line. (26th November 2021) - Zhang, Tianpeng; Zhai, Yafang; Wu, Zhanwei
According to the research status of a 35 kV microcomputer protection device, a new type of microcomputer protection and measuring-control device was designed to address common electrical failures during the running of 35 kV distribution line. In this device, a 32-bit high performance embedded microprocessor was used as the control centre, and the AD 7606 was used for analogue-to-digital conversion, which improves the data sampling accuracy. The device could realise real-time detection on electric parameters such as current, voltage, active power, reactive power, and provide the distribution line different protections, including current direction protection, over-current acceleration protection, zero sequence current direction protection and under frequency load shedding. In general, this device combines functions of protection, measurement, control and communication. With the characteristics of simple structure, easy operation, fully functioned and high reliability, this device also has high application value.